A sequência Fedathi e o jogo de tabuleiro: recursos metodológicos para o ensino de anatomia - Soares Neto, Josaphat (2023)
Anatomy teaching has as a common feature the development of traditional practices, where the teacher exposes a large amount of content in class and which are required in theoretical and practical tests. Thus, it becomes necessary to insert new pedagogical alternatives that can contribute to the improvement of the teaching and learning process. The research aims to analyze the impacts on the use of the board game in teaching practice based on the teaching proposal of the Fedathi Sequence (SF) in the Human Anatomy discipline for students in the health area, in particular, for students in the Class of Pharmacy at the Federal University of Ceará-UFC. The research presents itself as a descriptive and experimental exploratory survey with qualitative and quantitative approaches on the relationship and application of methodological resources in/for teaching in the health area, especially in the discipline of Anatomy. The study has as theoretical support Borges Neto (2001,2016,2017), Ausubel (2003). The theme highlighted in the anatomy study to be developed in the research was the Urinary System and the board game mediated by the Fedathi Sequence (SF) was adopted as methodological resources. The research was carried out in the Department of Morphology of the Faculty of Medicine of the Federal University of Ceará – UFC, with participants enrolled in the first semester of the health area, in particular, from the Pharmacy Course classes, professors and monitors. The validation of the board game had the selected presence of twenty expert judges, 19 (95%) working in teaching and one (05%) in research on anatomy. Pre-tests, post-tests and questionnaires were used as instruments for data collection. For statistical analysis, the GraphPad Prism 8.0.1 Kruskal-Wallis software was used, being considered significant when presented (p<0.0001). The results confirmed the validation of the board game in the pre-established criteria such as design, cards and relevance of the game with a general CVI of approximately 0,90 higher than the minimum of 0,78. As for the use of methodological resources in the Anatomy discipline, there was an increase in the number of correct answers in the pre-test and post-test and in the long-term tests when compared to traditional teaching, which proves a better qualification in the teaching-teaching process. learning. As for the pedagogical impacts on the use of resources, there is greater interaction in the dynamics of the class, enabling the construction of new knowledge in a cooperative way, promoting greater autonomy for the student, and providing opportunities for the development of meaningful learning, directly benefiting in their academic training and professional aptitude. As for the pedagogical impacts on the use of resources, there is greater interaction in the dynamics of the class, enabling the construction of new knowledge in a cooperative manner, promoting greater autonomy for the student, and providing opportunities for the development of significant learning, benefiting directly in their academic training and professional aptitude. Regarding the use of methodological resources in the Anatomy discipline, an increase in the number of correct answers in the pre-test and post-test and in the long-term tests was observed when compared to traditional teaching, which proves a better qualification in the teaching process- learning.